A decade of outcomes: The evolution of an australasian outcomes collaboration for chronic pain services - Holloway, David; Allingham, Samuel; Bryce, Meredith; Cameron, Kate; Cook, Michelle; Shebeshi, Dinberu (Frontiers in Pain Research, 2023)
Since the establishment of the electronic Persistent Pain Outcomes Collaboration (ePPOC) in 2013, ongoing improvements in benchmarking and quality improvement activities have provided the opportunity for ePPOC to grow to support more than one hundred adult and pediatric services delivering care to individuals living with persistent pain throughout Australia and New Zealand. These improvements straddle multiple domains, including benchmarking and indicators reports, internal and external research collaboration and the integration of quality improvement initiatives with pain services. This paper outlines improvements undertaken and lessons learned in relation to the growth and maintenance of a comprehensive outcomes registry and its articulation with pain services and the wider pain sector.